Off-types indicate natural outcrossing in five tropical forage legumes in Colombia - Maass, Brigitte L.; Torres González, Alba Marina (1998)
Flower colour has been used as a simple morphological marker for genetic studies in many species, including legumes. In several tropical forage legumes, grown to evaluate their environmental adaptation or forseed increase, white-flowered plants were observed when the predominant flower colour was either yellow (Chamaecrista rotundifolia) or pink, lilac or purple (Centrosema virginianum, Codariocalyx gyroides, Desmodium heterocarpon and Galactia striata). Open pollination of these 5 species took place each at 1 of 4 sites in Colombia. Progeny from white-flowered plants were examined for flower colour to assess the proportion of off-types. This ranged on average from 4% for D. heterocarpon, 13% for both G. striata and Ch. rotundifolia, and 18% for Ce. virginianum, to 23% for Co. gyroides. Large differences were recorded among accessions of the same species, particularly in Ce. virginianum, where 4 of the accessions apparently produced autogamous offspring and the other 5 had high proportions of off-types, with a rate as high as 89%. Consequences of these results for germplasm collection, management and seed increase are discussed.